Telaah Normatif Penerapan Peraturan Penyelesaian Sengketa Kepemilikan Sertifikat Hak Atas Tanah Tumpang Tindih (Overlapping) Di Kabupaten Banyuasin - Kurniati, Kurniati (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Land has a value that can provide benefits to humans both economically, socially and politically. For Indonesian people who are agrarian, land is the main medium for finding a source of life. So important is land for human life that everyone will always try to own it and control it. Carry out orderly land tenure both at the Kelurahan/Village level, up to the District/City Land Office. The rules for land use are orderly law, orderly administration, orderly use of land and orderly maintenance of the environment; Increase supervision of measuring officers from BPN by their superiors. In the legal aspect, deliberation and consensus should be prioritized in resolving disputes over overlapping land rights. The National Land Agency, as the executor of land administration, in carrying out its duties and functions, must further increase its thoroughness, precision and accuracy, supported by strong map data. It is better if the National Land Agency is given the authority to carry out a judicial review of an application for the issuance of a right so that this overlapping certificate does not happen again. Apart from that, don't let the land for which the certificate has been issued be left empty, it is better if the land is utilized so that legal certainty for the land is guaranteed.